Oral and Written Production of Iranian English Learners: Scale of Fluency, Grammatical accuracy, Grammatical complexity and Lexical complexity - Kavandi, Elham (IJRDO- Journal of Educational Research, 2020)
This study is an attempt to explore fluency, grammatical accuracy, grammatical complexity and lexical complexity among female student teachers of English in West Azerbaijan, Iran. To find out the students four measures in the oral and written productions, we asked the individual participants to write a narrative out of the practical sequence of the story and retell the same story orally after several hours. We repeated this process for three weeks.  We obtained and analyzed the data using the formula of fluency, grammatical accuracy, grammatical complexity and lexical complexity. The result showed that the participant’s performance in written form developed progressively. but only in one case it developed regressively. In oral form the development followed different pattern in different cases.